Convergence of the Bregman extragradient method - Vedel, Ya.I.; Denisov, S.V.; Semenov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
The convergence of a new extragradient-type method for the approximate solution of variational inequalities with pseudomonotonіс and Lipschitz-continuous operators acting in a finite-dimensional linear normed space is proved. The method uses the Bregman divergence instead of the Euclidean distance and the new adjustment of the step size, which does not require knowledge of the Lipschitz constant of an operator. In contrast to the previously used rules for choosing the step size, the proposed method does not perform additional calculations for the operator values and prox-map.